Replication Data for "Food Transfers, Electronic Food Vouchers and Child Nutritional Status Among Rohingya Children Living in Bangladesh" - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is a cleaned subset of a household survey conducted in and around the Rohingya settlement camps in Southeastern Bangladesh. The data underlines the study “Food transfers, electronic food vouchers and child nutritional status among Rohingya children living in Bangladesh." It includes anthropometry of 523 children aged between 6 and 23 months in households receiving either a food ration consisting of rice, pulses, vegetable oil (362 children) or an e-voucher (161 children) that could be used to purchase 19 different foods. In addition, this dataset also provides information on the characteristics of the mothers and the households in which they lived, including household demographics, consumption and expenditure, coping strategies, livelihoods and income profiles, and access to assistance.